The Scheherazade Romance in Ahdaf Soueif’s In the Eye of the Sun, Leila Aboulela’s The Translator and Fadia Faqir’s My Name is Salma - Akkawi, Aya; Maqableh, Rasha (Jordan Journal of Modern Languages & Literatures, 2025)
Many Arab, female Anglophone writers have taken the lead to showcase new dimensions of women empowerment in their works of fiction. One of these dimensions includes a plot we coined as the Scheherazade Romance. This coined term allocates Arab, Muslim women as heroines and White, Western men as heroes when defining the romance they experience. This paper aims at providing a new conceptual framework added to the subgenres of the romance, the Scheherazade Romance. The female characters (emblems of Scheherazade) challenge the conventional identity tropes of their culture, and go through with the shape-shifting forces of their lives. This similar shift in their identities come to explain their enhanced agency, forms of resistance, and their ability to achieve trans-cultural harmony with racially and culturally ’other’ man. Thus, the study examines the following literary works— Ahdaf Soueif’s In the Eye of the Sun, Leila Aboulela’s The Translator and Fadia Faqir’s My Name is Salma —which relate to this concept. Keywords: The Scheherazade Romance, Female Anglophone Writers, In the Eye of the Sun, The Translator, My Name is Salma.